The Influence of Taxpayer Awareness, Tax Knowledge, Service Quality, Tax Sanctions, and Tax Audits on Tax Compliance of Restaurant Taxpayers - Nurdiana, Aria; Maulina, Anita; Wahyudin, Dian; Zaini, Zaman; Hendrarso, Panji (Jurnal Locus Penelitian dan Pengabdian, 2025)
Local Revenue (PAD) or Local Own-Source Revenue (LOSR) is an important component in the local government budget, with Specific Goods and Services Tax (PBJT) as one of the main sources. In the Special Capital region of Jakarta, PBJT on Food and Beverages (previously known as Restaurant Tax) has become the most significant sector in contributing to PAD. However, taxpayer compliance in this sector remains a challenge, as evidenced by restaurant tax arrears reaching IDR 141.3 billion in 2023. This study aims to analyze the influence of taxpayer awareness, tax knowledge, service quality, tax sanctions, and tax audits on taxpayer compliance in the restaurant sector in Central Jakarta. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to restaurant taxpayers and analyzed using the Partial Least Square Structural Equation Modeling (PLS SEM). Results of the study indicate that sanctions and service quality have a positive and significant effect on taxpayer compliance. However, the findings show that taxpayer awareness, tax knowledge, and tax audits do not significantly influence taxpayer compliance. Findings suggest that strategies to improve tax compliance should focus on enhancing service quality and implementing more optimal sanctions. With these efforts, it is hoped that local tax revenue from the restaurant sector can continue to increase and support sustainable regional development.